2021
DOI: 10.1002/bin.1792
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of the impact of stimulus mode on acquisition, maintenance, and generalization of tacts of actions

Abstract: Individuals with an autism spectrum disorder or communication delay may experience deficits in tacting. Furthermore, children, with and without language impairments, acquire tacts of objects earlier than tacts of actions, suggesting that tacts of actions may be more difficult to learn (e.g., Sheng & McGregor, 2010). One variable that may impact acquisition of tacts of actions is the type of stimulus (e.g., picture of the action; video of the action) used during training. This study compared acquisition of tact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
1
0
Order By: Relevance
“…In four of these studies, a preference could not be established for at least one participant due to responses being allocated across multiple initial links. That is, there was no consistent selection of the same stimulus (Bergmann et al, 2023; Galizio et al, 2020; Lozy et al, 2020; Mandel et al, 2022). Two of these studies indicated a lack of a control condition as a limitation (i.e., Bergmann et al, 2023; Galizio et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…In four of these studies, a preference could not be established for at least one participant due to responses being allocated across multiple initial links. That is, there was no consistent selection of the same stimulus (Bergmann et al, 2023; Galizio et al, 2020; Lozy et al, 2020; Mandel et al, 2022). Two of these studies indicated a lack of a control condition as a limitation (i.e., Bergmann et al, 2023; Galizio et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…Video models first developed To provide a motivating environment for the child participants, preferred materials (e.g., toys, sensory items, art activities) were identified using the Reinforcer Assessment for Individuals with Severe Disability (RAISD; Fisher et al, 1996). This parent interview tool has been used to establish preferred stimuli for young children with ASD in intervention research Mandel et al, 2022). After preferred items were established, two unique targeted sets of materials were created for each child-one set for the child to use in student clinician-led sessions and one set for parent-led sessions.…”
Section: Setting and Materialsmentioning
confidence: 99%